Early collapse causing stenosis in a resorbable magnesium scaffold. Issue 2 (18th July 2018) - Marynissen, Thomas; McCutcheon, Keir; Bennett, Johan
Abstract: We report a case of early in‐stent restenosis due to collapse of a Magmaris resorbable magnesium scaffold.